2020
DOI: 10.3762/bjoc.16.127
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical green synthesis of hyper-crosslinked cyclodextrin polymers

Abstract: Cyclodextrin nanosponges (CD-NS) are nanostructured crosslinked polymers made up of cyclodextrins. The reactive hydroxy groups of CDs allow them to act as multifunctional monomers capable of crosslinking to bi- or multifunctional chemicals. The most common NS synthetic pathway consists in dissolving the chosen CD and an appropriate crosslinker in organic polar aprotic liquids (e.g., N,N-dimethylformamide or dimethyl sulfoxide), which affect the final result, especially for potential biomedical applications. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…Significant advances on the synthesis of CD-NSs [39], and their applications ranging from the environment [40] to other fields such as pharmacy, chemistry, agriculture, gene delivery, biomedicine and biotechnology, food, cosmetics, biocatalysis, etc., [6][7][8][9][10]22] have emerged over years. As judged from the historical development of CD-NSs [39], they have been the subject of numerous surveys, heading towards greener processes such as the CD-NSs synthesis in natural deep eutectic solvents (NADES) [41] and solvent-free CD-NSs synthesis [42]. Studies performed on the polymeric structure of ester-bridged βCD-NSs based on PMDA [27,[43][44][45] showed that the crosslinking degree is strongly dependent on the PMDA:β-CD molar ratio used during the CD-NSs synthesis, related to the swelling capacity as an important parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Significant advances on the synthesis of CD-NSs [39], and their applications ranging from the environment [40] to other fields such as pharmacy, chemistry, agriculture, gene delivery, biomedicine and biotechnology, food, cosmetics, biocatalysis, etc., [6][7][8][9][10]22] have emerged over years. As judged from the historical development of CD-NSs [39], they have been the subject of numerous surveys, heading towards greener processes such as the CD-NSs synthesis in natural deep eutectic solvents (NADES) [41] and solvent-free CD-NSs synthesis [42]. Studies performed on the polymeric structure of ester-bridged βCD-NSs based on PMDA [27,[43][44][45] showed that the crosslinking degree is strongly dependent on the PMDA:β-CD molar ratio used during the CD-NSs synthesis, related to the swelling capacity as an important parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we demonstrated the possibility a CD-NS, having the same characteristics as cyclodextrin-based polymers synthesized in batch, to be obtained without the use of any solvents, via a mechanochemistry-driven reaction in ball mill (Rubin Pedrazzo et al 2020 ; Trotta and Rubin Pedrazzo 2021 ). The reaction reported is completely carried out by mixing/grinding the dry CDs powder with the cross-linker, 1,1-carbonyldiimidazole (CDI).…”
Section: Introductionmentioning
confidence: 99%
“…The potential pharmaceutical applications require removal not only of the solvent but also of unreacted and degraded reagents. The suppressed decomposition of the reagents makes the workup of the nanosponge crude products prepared in BM simple, and the filtration of the water-insoluble residual reagents can provide high purity products [ 95 ].…”
Section: Discussionmentioning
confidence: 99%